2020
DOI: 10.1002/cplu.202000639
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Supertetrahedral Tn Chalcogenido Clusters Synthesized in Ionic Liquids: Crystal Structures and Photocatalytic Activity

Abstract: Discrete supertetrahedral Tn chalcogenido clusters, which can be regarded as the smallest semiconductor quantum dots with precise chemical composition, have attracted considerable attention due to their outstanding photoluminescent, photoelectric, and photo/electrocatalytic properties. Such discrete molecular clusters are suitable for solution processing towards functional materials and can be used as precursors for constructing open‐framework chalcogenides. Traditionally they were synthesized hydro(solvo)ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 120 publications
(325 reference statements)
0
14
0
Order By: Relevance
“…Traditionally, chalcogenides containing supertetrahedral clusters have been synthesized by high-temperature methods (for purely inorganic solids) or by solvothermal synthesis, in which water or amines are often used as solvents. More recently, the ionothermal method, in which an ionic liquid acts as both the solvent and the structure-directing agent [ 20 ], has been successfully exploited for the preparation of chalcogenides [ 4 , 21 ]. Benefits of the ionothermal approach include the ability to carry the synthesis at ambient pressures and the absence of competition between the solvent and the structure directing agent.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Traditionally, chalcogenides containing supertetrahedral clusters have been synthesized by high-temperature methods (for purely inorganic solids) or by solvothermal synthesis, in which water or amines are often used as solvents. More recently, the ionothermal method, in which an ionic liquid acts as both the solvent and the structure-directing agent [ 20 ], has been successfully exploited for the preparation of chalcogenides [ 4 , 21 ]. Benefits of the ionothermal approach include the ability to carry the synthesis at ambient pressures and the absence of competition between the solvent and the structure directing agent.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of the ionothermal approach include the ability to carry the synthesis at ambient pressures and the absence of competition between the solvent and the structure directing agent. Ionothermal synthesis has been found to be advantageous for the synthesis of discrete supertetrahedral clusters [ 4 ]. It has been suggested that anion-π interactions between chalcogen ions and the organic cations in the ionic liquid may increase the stability of discrete clusters and, under ionothermal conditions, the chalcogens normally at the four corners of the clusters may be easily replaced by the halogens or organic ligands, which reduce the local negative charge and prevent the formation of extended structures [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations